Subscription vacations. The subscription economy in the tourism market: The case study of Poland - Markiewicz, Ewa; Ziobrowska-Sztuczka, Justyna (Quaestiones Geographicae, 2025)
The purpose of the article is to identify the scale of application of subscription models in the tourism market in Poland and to analyse experiences of Polish consumers using this model. The study was based on a literature review, case studies, and an online Computer Assisted Web Interview (CAWI) survey among 350 respondents, 190 of whom used travel subscriptions. Guided by three research questions and two hypotheses, the analysis focused on the prevalence of travel subscriptions, the perceived benefits, and the influence of socio-demographic factors. The results have confirmed that booking platforms (33.1%) and accommodation (27%) are the most frequently used subscriptions, and that discounts (64.3%) and booking flexibility (44.1%) are key benefits, while personalisation and exclusivity play a secondary role. Age and income were found to significantly differentiate subscription usage and preferences, thus partially confirming the hypotheses. These findings provide practical recommendations for tourism companies on how to design, segment, and implement subscription models, which can help stabilise revenues and address the seasonality of tourism demand.